KARAKTERISTIK SAMPAH DAN PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN SAMPAH DI KECAMATAN BANYUWANGI KABUPATEN BANYUWANGI PROVINSI JAWA TIMUR - Maharani, Shinta E.; Suarna, I Wayan; Budiarsa Suyasa, I W. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
This study concern waste characteristics and community’s perception of waste management in Banyuwangi District, Banyuwangi Regency, East Java Province. It was conducted in February up to August 2006. It aims to (1) know waste characteristics in the Bulusan Final Disposal Area (TPA) in the service area of Banyuwangi District compared with that in the service area of Kalipuro District, Banyuwangi Regency, (2) know the perception and role of the component of waste producers that cover household, tourism supporting industry, and government institution having the authority in waste management in Banyuwangi District, Banyuwangi Regency, East Java Province to waste management in determining the pattern of its management, and (3) know the alternative of the suitable pattern of waste management to be applied in Banyuwangi Regency and the surrounding areas. The study was conducted with direct observation to the TPA Bulusan, distributing questionnaire, and conducting direct interview with some government institutions that deal with the service of waste management. The questionnaire data to get the community’s perception were analyzed by means of forcefield analysis to obtain the positive and negative value of the existing problems. The findings show that (1) Banyuwangi District has the biggest percentage of organic waste characteristics spread among other wastes such as plastic, paper, textile, and glass waste, (2) socio-economic factor of the household waste has the highest positive value compared with the component of tourism supporting and government institution. Banyuwangi Regency’s community’s perception as a whole has positive value and support the effort by finding a better solution to the problem, and (3) the suitable alternative of the pattern of waste management to be applied in Banyuwangi District and the surrounding areas is the development of human resources, the addition of educational curriculum, economic improvement, the improvement of facilities and infrastructure, introduction of local regulations, and the forming of media for the community.
Keywords: waste characteristics, community’s perception, management pattern.